Analisis TPACK dalam Pembelajaran Matematika pada Materi Turunan Fungsi Aljabar dengan Dukungan WhatsApp - Melati, Catur Yustika; Juandi, Dadang; Jupri, Al (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2025)
This research aims to describe a comprehensive learning process on how technology, pedagogy and content knowledge are integrated in the learning process. An observational qualitative study was used to conduct the research involving 35 students and 1 mathematics teacher in a senior high school in West Java. The results showed that from the aspect of Pedagogical Knowledge (PK), the teacher showed a good ability in conveying derivative concepts with varied methods. In terms of Content Knowledge (CK), teachers have a good and in-depth understanding of the derivative material of algebraic functions and are able to answer student questions clearly and provide relevant examples. In terms of Technological Knowledge (TK), the use of technology both low tech (markers and blackboard) and digital technology (WhatsApp) shows how technology can be used to facilitate learning. Overall, this observation shows that good integration of pedagogical, content and technological knowledge can improve learning effectiveness and students' understanding of the concept of algebraic function derivative.